New Perspectives To Reduce Stress Through Digital Humor - Misnal Munir; Amaliyah; Moses Glorino Rumambo Pandin (Airlangga Development Journal, 2022)
This study aimed to find new perspectives on the use of humor through digital media. A qualitative approach was used to conduct this study, where data were collected through literature review. Stress is caused by the inability of a person to adapt between desires and reality. All forms of stress are basically caused by a lack of understanding of human's own limitations. Inability to fight limitations that will cause frustration, conflict, anxiety and guilt. Too much stress can threaten a person's ability to deal with the environment. As a result, employees develop various kinds of stress symptoms that can interfere with their work performance. Thus, the management of work stress is important to do, one of which uses humor. However, in the digital age the spread of humor can be easily facilitated. The results of this review article find new perspectives to reduce stress through digital humor, namely interactive humor, funny photos, manipulations, phanimation, celebrity soundboards, and PowerPoint humor. The research shows that the use of humor as a coping strategy is able to predict positive affect and well-being work related. Moreover, digital humor which has various forms as well as easy, fast and wide spread, then the effect is felt increasingly significant